Extraction and Purification of Sulfated Polysaccharide from Brown Algae and its Efficacy in Preventing Blood Clotting - Jayaraman, Jamuna Devi; Sigamani, Santhosh; Venkatachalam, Hemalatha; Ramamurthy, Dhandapani (Asian Journal of Biological and Life Sciences, 2016)
The three brown algae Sargassum wightii, Padina tetrastromatica and Dictyota sp., collected from CS-MCRI, CSIR Institute, Mandapam coast, Rameshwaram, India. Extraction was carried out using HCl extraction method .The maximum yield of sulfated polysaccharide (3.91g) was obtained from Sargassum wightii. The Lyophilized powders of all the three sulfated polysaccharides (SPs) were further processed for estimation of carbohydrate, sulfate and protein content. The highest content of carbohydrate (240μg/mL), sulfate (127 μg/mL) and protein (176 μg/mL) were observed in Sargassum wightii. These SPs were characterized by high-performance liquid chromatography and FTIR which verified the presence of fucose and galactoseas main components (70:30% mol ratio in average). The HPLC profile of the three SPs showed prominent peaks and the retention time was obtained in 5.2 to 5.4. The FTIR spectrum of the three samples showed characteristic absorbance bands of sulfated polysaccharide. The in vitro anticoagulant activity of the SPs were investigated and compared. The high APTT values indicated that the crude from S. wightii (31.3±1) have high anticoagulation activity followed by P. tetrasromatica (29.7±1.1) and from Dictyota sp. (28 ± 1.03).
Keywords: Anticoagulant; Brown algae; Extraction; FTIR; HPLC; Sulfated Polysaccharide